Application of Index Card Match Learning Method in Mastery of Arabic Vocabulary - Albaiyah, Albaiyah; Nasution, Sahkholid (STUDI ARAB, 2024)
The problem at Madrasah Aliyah Negeri 2 Langkat is that there are still many students who consider learning Arabic to be a boring and monotonous lesson, resulting in students lacking mastery of the material, especially in vocabulary mastery. Researchers try to solve this problem by using the Index Card Match learning model. This study aims to determine the application of Index Card Match learning in students' mastery of Arabic vocabulary. This study uses a descriptive qualitative approach, this study method includes classroom observation, documentation and interviews with teachers and students. The Index Card Match method in class XI MAN 2 Langkat allows students to play an active role in group learning by competing with each other in finding the right card pair. The results of the study show that the application of the Index Card Match method can have a positive impact on students' active learning of Arabic vocabulary and also increase from before. Students are more active in asking the teacher about their own ideas and other people's ideas and answering questions, more enthusiastic about paying attention to the teacher when explaining the lesson, listening to the description, enthusiastic and responsive in looking for pairs of question cards and answers.